Critical care nursing clinics of North America : pediatric illnesses and transition of care - Aquino, Victor M.; Bashore, Lisa M.;Chacko, Jisha;Clark, Lynn;Foglia, Dorothy C.;Gillette, Paul C.;Howe, Carol J.;Kolins, Julie A.;Zeigler, Vicki L. ;Foster, Janet (Philadelphia, Pennsylvania : Saunders, 2011)
Focuses on Pediatric Illnesses and the Transition of Care. This book covers topics that range from the past, present and future of pediatric critical care nursing, postoperative rhythm disturbances after surgery for congenital heart disease, and chronic illnesses in children and the transition to adulthood.
The evolution of pediatric critical care nursing: past, present, and future -- Acute cardiac arrhythmias following surgery for congenital heart disease: mechanisms, diagnostic tools, and management -- Use of continous glucose monitoring systems in children with type 1 diabetes -- Pain management in the pediatric population -- The 2010 American Heart Association Guidelines for cardiopulmonary resuscitation and emergency cardiac care: an overview of the changes to pediatric basic and advanced life support -- Young adults with risk actors for chronic disease: transition needs for survivors of childhood cancer -- Pediatric sepsis and multiorgan dysfuction syndrome: progress and continued challenges -- Transcatheter device closure for atrial septal defects: safety, efficacy, complications, and costs -- Hematopoietic stem cell transplantation in children -- Ethical considerations in pediatric critical care research
Includes bibliographical references and index.
Keywords: CHRONIC DISEASES